Geographic structure in the Southern Ocean circumpolar brittle star Ophionotus victoriae (Ophiuridae) revealed from mtDNA and single‐nucleotide polymorphism data. Issue 2 (16th December 2016) - Galaska, Matthew P.; Sands, Chester J.; Santos, Scott R.; Mahon, Andrew R.; Halanych, Kenneth M.
Abstract: Marine systems have traditionally been thought of as "open" with few barriers to gene flow. In particular, many marine organisms in the Southern Ocean purportedly possess circumpolar distributions that have rarely been well verified. Here, we use the highly abundant and endemic Southern Ocean brittle star Ophionotus victoriae to examine genetic structure and determine whether barriers to gene flow have existed around the Antarctic continent. Ophionotus victoriae possesses feeding planktotrophic larvae with presumed high dispersal capability, but a previous study revealed genetic structure along the Antarctic Peninsula. To test the extent of genetic differentiation within O. victoriae, we sampled from the Ross Sea through the eastern Weddell Sea. Whereas two mitochondrial DNA markers (16S rDNA and COI) were employed to allow comparison to earlier work, a 2b‐RAD single‐nucleotide polymorphism (SNP) approach allowed sampling of loci across the genome. Mitochondrial data from 414 individuals suggested three major lineages, but 2b‐RAD data generated 1, 999 biallelic loci that identified four geographically distinct groups from 89 samples. Given the greater resolution by SNP data, O. victoriae can be divided into geographically distinct populations likely representing multiple species. Specific historical scenarios that explain current population structure were examined with approximate Bayesian computation (ABC) analyses. Although the Bransfield Strait region shows high diversity possibly due to mixing, our results suggest that within the recent past, dispersal processes due to strong currents such as the Antarctic Circumpolar Current have not overcome genetic subdivision presumably due to historical isolation, questioning the idea of large open circumpolar populations in the Southern Ocean. Abstract : Phylogeography of Southern Ocean circumpolar brittle star Ophionotus victoriae was investigated from the Ross Sea through the eastern Weddell Sea, a distance of >7, 000 km. Use of mtDNA and nuclear single‐nucleotide polymorphism data both revealed geographic structure through this range. In particular, the western Antarctic Peninsula and Weddell Sea are an area of high genetic diversification, while the Bellingshausen Sea appears genetically unique or possibly isolated.